Applied econometric time series - Enders, Walter 1948- (Wiley series in probability and statistics, 2010)
"This introduction to time-series analysis shows how to develop models capable of forecasting, interpreting, and testing hypotheses concerning economic data using the modern techniques. Numerous real-world examples from fields ranging from agricultural economics to transnational terrorism further illustrate the various techniques. ... The new edition reflects both sound structure and recent advances in time-series econometrics, such as out-of-sample forecasting techniques, nonlinear time-series models, Monte Carol analysis and bootstraping."--Book jacket.